Hierarchical search-based routing protocol for infrastructure-based opportunistic networks. (18th March 2021) - Sharma, Deepak Kumar; Dhurandher, Sanjay Kumar; Kumar, Shiv
Opportunistic networks (OppNets) consist of intermittently connected devices where there is no guarantee that a predefined path from source to destination for message transmission exists. In such a sparsely connected network where nodes relay messages in an opportunistic manner, designing a routing protocol is a challenging task. In this paper, a novel routing protocol for infrastructure-based OppNets called the hierarchical search-based routing protocol (HSBRP) has been proposed. This protocol combines the benefits of both fixed and mobile routing techniques, combating the disadvantages posed by each, to give better performance on a multitude of performance metrics like, no single point of failure, fault detection and communication capacity, etc. In the proposed protocol, nodes are arranged in a hierarchical fashion and interactions between different levels of nodes are only allowed through well-defined rules that boost message delivery probability and reduce the overhead of the network.